THE IMPACT OF TIKTOK SOCIAL MEDIA ON SCIENCE LEARNING OUTCOMES: A STUDY OF 5TH GRADE STUDENTS AT ST. YOSEPH CATHOLIC THREE ELEMENTARY SCHOOL IN KUPANG CITY - Maria Anastasia Rato Kopa; Asti Yunita Benu; Vera Rosalina Bulu (Universitas Citra Bangsa, 2024)
This research was conduct to analyze the effectivity of TikTok as a learning media in improving science learning outcome especially at 5th-grade students of St. Yoseph Catholic Three Elementary School of Kupang. The research utilized a quasi-experimental design with an experimental group being taught by TikTok videos and a control group by conventional teaching. Pre- and post-test results were reported as well as observations from the classroom data. Results showed significant change in scale among students of experimental group as compared to control group for respiratory system understanding. It was revealed that the introduction of TikTok made students more interactively engage in content and collective discussions assuring their motivation as well. Although there were a few limitations, differences of opinion on content precision when assessed, and perceptions towards TikTok as an entertainment platform that were prevailing challenges the results from this study suggest that TikTok can enhance learning outcomes in elementary science education. The implications are that educators should start to think about using TikTok as an educational tool, which could lead toward engaging and interactive learning spaces.